A hydrogel electrode with anti-fatigue bonding properties and its preparation method and application

By preparing hydrogel electrodes with anti-fatigue bonding properties, the problem of interfacial fatigue caused by energy dissipation in existing hydrogel electrodes during long-term use is solved, and more stable interfacial bonding and longer service life are achieved. .

CN116115781BActive Publication Date: 2025-02-11SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211580013.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-09
Publication Date
2025-02-11
Estimated Expiration
2042-12-09

AI Technical Summary

Technical Problem

During long-term use of existing hydrogel electrodes, the interface fatigue threshold has decreased due to energy dissipation, resulting in the hydrogel layering and falling off from the surface of the working electrode, making it difficult to build a stable interface.

Method used

By providing an electrode matrix and a hydrogel precursor, including a polyvinyl alcohol solvent, a conductive polymer precursor and an oxidant, it is subjected to activation treatment, freezing-thawing cycle treatment, drying and heat treatment, hydrocoagulation with anti-fatigue bonding properties is prepared by performing activation treatment, freezing-thawing cycle treatment, drying and heat treatment. Glue electrode.

Benefits of technology

It improves the anti-fatigue bonding performance of hydrogel electrodes, extends the interface stability, and ensures stable interface bonding between the hydrogel coating and the electrodes, and is suitable for long-term operation of bioelectronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116115781B_ABST
    Figure CN116115781B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of biomedical materials, and discloses a hydrogel electrode with anti-fatigue bonding properties and a preparation method and application thereof, the method comprising the steps of: activating an electrode substrate to obtain an activated electrode substrate; adding a conductive polymer precursor and an oxidant to a polyvinyl alcohol solution, and mixing to obtain a hydrogel precursor solution; applying the hydrogel precursor solution to the surface of the activated electrode substrate, first subjecting it to a freeze-thaw cycle treatment, then subjecting it to a drying treatment, and finally subjecting it to a heat treatment to obtain an initial hydrogel electrode; and subjecting the initial hydrogel electrode to a post-treatment to obtain a hydrogel electrode with anti-fatigue bonding properties. In the hydrogel electrode prepared by the present invention, since the hydrogel has a high degree of crystallinity after thermal annealing, a high-energy unit can be generated at the bonding interface, which can improve the anti-fatigue performance of the hydrogel bonding, ensure stable interface bonding between the hydrogel coating and the electrode, and the characteristics of anti-fatigue bonding in long-term operation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biomedical materials, and in particular to a hydrogel electrode with anti-fatigue bonding properties and a preparation method and application thereof. Background Art

[0002] With the rapid progress of semiconductor and microelectronics manufacturing technology, various electronic devices have been driven towards miniaturization / micro-miniaturization / multi-functionality. Many wearable and implantable electronic devices have been developed, which can be used to collect various physiological signals (such as electromyographic signals, electrocardiographic signals, and electroencephalographic signals) generated by different parts of the body, or to treat diseases in the body. Compared with wearable electronics, implantable bioelectronic devices act directly on the tissue interface in the body, can provide more accurate physiological information data of the body, and conduct early intervention and treatment of diseases in the body, which is a powerful tool for biomedical research.

[0003] At present, several common implantable electronic devices in medicine include deep brain stimulators, cochlear implants, and pacemakers. These devices usually seal the electronic module in a rigid shell and directly act on biological tissues by connecting metal electrodes. However, the modulus level of metal electrodes (1GPa) is much higher than that of biological tissues (1-100kPa). Direct action on biological tissues can cause tissue damage, inflammatory response and other problems; in addition, tissue fibrosis will occur on the electrode surface, resulting in decreased electrode function, which will not be able to play a therapeutic role. One of the most effective ways at present is to coat a layer of hydrogel on the surface of the rigid electrode to reduce the damage caused by the electrode to biological tissue. Hydrogels have a modulus level that matches biological tissues, as well as high water content and biocompatibility. In recent years, they have been widely used in fields such as tissue engineering and biomedicine. Therefore, as a buffer layer between rigid electrodes and soft tissues, hydrogel coatings can effectively alleviate challenges such as mechanical mismatch between electrodes and tissues. Hydrogels can be coated or grown on substrates of any shape. They are currently widely used in various epidermal / implantable medical devices as conductive, adhesive or lubricating coatings. In addition, hydrogel coatings can also be given some new functions, such as drug release, antibacterial / antifouling / oil resistance, etc. However, since hydrogels have a high water content (>80%) and a very low elastic modulus (1-100kPa), electronic devices are all water-free and have a high elastic modulus (>1GPa), which makes it difficult for hydrogels to construct a long-term stable interface. Recent researchers have found that by treating the surface of the substrate (grafting amino groups or unsaturated double bonds), a covalent bond can be formed between the hydrogel and the substrate. This method can achieve good adhesion between the hydrogel and the engineering material (Nature Materials 2016,15,190). Although the above method can achieve high-toughness adhesion between hydrogels and various engineering materials, hydrogel electrodes usually need to be used for a long time in the body. Under long-term operation conditions, the energy dissipation inside the hydrogel will be significantly reduced, resulting in a rapid decrease in the interface fatigue threshold (i.e., the minimum fracture energy required for interface fatigue crack propagation), causing the hydrogel to delaminate and fall off from the surface of the working electrode, making it difficult to construct a stable hydrogel electrode coating.

[0004] Therefore, the prior art still needs to be improved and developed. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a hydrogel electrode with anti-fatigue bonding properties and a preparation method and application thereof, aiming to solve the problem that the existing hydrogel coating has poor anti-fatigue bonding properties, resulting in its instability at the electrode interface.

[0006] The technical solution of the present invention is as follows:

[0007] A method for preparing a hydrogel electrode with anti-fatigue bonding properties, comprising the steps of:

[0008] Providing an electrode matrix and a hydrogel precursor solution, wherein the hydrogel precursor solution includes a polyvinyl alcohol solvent and a conductive polymer precursor and an oxidant dispersed in the polyvinyl alcohol;

[0009] Performing an activation treatment on the electrode matrix to obtain an activated electrode matrix;

[0010] The hydrogel precursor solution is applied to the surface of the activated electrode substrate, firstly subjected to a freeze-thaw cycle treatment, then subjected to a drying treatment, and finally subjected to a heat treatment to obtain an initial hydrogel electrode;

[0011] The initial hydrogel electrode is immersed in deionized water or PBS solution, and taken out to obtain the hydrogel electrode with anti-fatigue bonding properties.

[0012] The method for preparing the hydrogel electrode with anti-fatigue bonding properties, wherein the electrode substrate is a platinum electrode, a gold electrode, a stainless steel electrode, a magnesium electrode, ITO-glass, ITO-PET, a carbon electrode, and an electrode whose surface is coated with a conductive material.

[0013] The method for preparing the hydrogel electrode with anti-fatigue bonding properties, wherein the step of activating the electrode substrate comprises:

[0014] The electrode substrate is sequentially immersed in deionized water, ethanol, and acetone for ultrasonic cleaning, each ultrasonic cleaning lasts for 5-15 minutes, and repeated three times, and dried under nitrogen conditions to obtain a cleaned electrode substrate;

[0015] The surface of the cleaned electrode substrate is cleaned with oxygen plasma and activated for 5-30 minutes to obtain an activated electrode substrate.

[0016] The method for preparing a hydrogel electrode with anti-fatigue adhesion properties, wherein the conductive polymer precursor is one or more of acetylene, thiophene, 3-methylthiophene, 3-hexylthiophene, aniline, aminophenylboronic acid, pyrrole, furan, indole, 5-nitroindole, 5-carboxylic acid indole, p-phenylene vinylene, 3,4-ethylenedioxythiophene, 2'-aminomethyl-3,4-ethylenedioxythiophene and hydroxymethyl (3,4-ethylenedioxythiophene).

[0017] The method for preparing the hydrogel electrode with anti-fatigue bonding properties, wherein the oxidant is one or more of iodine, ammonium persulfate, ferric chloride, ferric p-toluenesulfonate, hydrogen peroxide, potassium dichromate and potassium permanganate.

[0018] The method for preparing the hydrogel electrode with anti-fatigue bonding properties, wherein the polyvinyl alcohol solution is a polyvinyl alcohol aqueous solution with a mass fraction of 3%-20%, and the molecular weight of the polyvinyl alcohol is 1000-300000Da.

[0019] The preparation method of the hydrogel electrode with anti-fatigue bonding properties, wherein the freeze-thaw cycle treatment step includes: first freezing at a temperature of -30°C to 0°C for 5-8 hours, and then thawing at a temperature of 0°C to 40°C for 1-3 hours, and the number of cycles is 1-10 times; the drying treatment step includes: drying under air or nitrogen conditions for 3-48 hours; the heat treatment step includes: heating at a temperature of 60°C to 150°C for 0.5-24 hours.

[0020] A hydrogel electrode with anti-fatigue bonding properties, wherein the hydrogel electrode is prepared by the preparation method of the hydrogel electrode with anti-fatigue bonding properties of the present invention, the hydrogel electrode comprises an electrode substrate and a hydrogel coating bonded to the surface of the electrode substrate, and the material for preparing the hydrogel coating comprises polyvinyl alcohol and a conductive polymer.

[0021] The hydrogel electrode with anti-fatigue adhesion properties, wherein the conductive polymer is one or more of polyacetylene, polythiophene, poly(3-hexylthiophene), polyaniline, polypyrrole, polyfuran, polyindole, poly(p-phenylene vinylene), poly(3,4-ethylenedioxythiophene) and poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate).

[0022] An application of a hydrogel electrode with fatigue-resistant bonding properties, wherein the hydrogel electrode is used in an implantable biosensor, a pacemaker, or a neural electrode.

[0023] Beneficial effects: The present invention provides a hydrogel electrode with anti-fatigue bonding properties. Since the PVA hydrogel has a high degree of crystallinity after thermal annealing, a high-energy unit (such as an ordered nanocrystalline domain) can be generated at the bonding interface, which can significantly improve the anti-fatigue performance of the hydrogel bonding and increase the interface fatigue threshold of the hydrogel, thereby ensuring stable interface adhesion between the hydrogel coating and the electrode, as well as anti-fatigue bonding properties in long-term operation. The hydrogel electrode provided by the present invention can be applied to a variety of bioelectronic devices, such as implantable biosensors, cardiac pacemakers or neural electrodes, etc. The use of hydrogel-coated electrodes can effectively reduce the damage caused by the electrodes to biological tissues, and the hydrogel coating can effectively reduce the electrochemical impedance of the metal electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The present invention is a flow chart of a method for preparing a hydrogel electrode with anti-fatigue bonding properties.

[0025] Figure 2 This is a comparison chart of the adhesion performance test results between the electrode and the hydrogel coating in the hydrogel electrode prepared in Example 1 of the present invention and the PEDOT:PSS electrode prepared in Comparative Example 1.

[0026] Figure 3 This is a graph showing the cyclic voltammetric stability test results of the hydrogel electrode prepared in Example 1 of the present invention before and after ultrasound. DETAILED DESCRIPTION

[0027] The present invention provides a hydrogel electrode with anti-fatigue bonding properties and a preparation method and application thereof. In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0028] See also Figure 1 , Figure 1 A flow chart of a method for preparing a hydrogel electrode with anti-fatigue bonding properties provided by the present invention is shown in the figure, which comprises the steps of:

[0029] S10, providing an electrode matrix and a hydrogel precursor solution, wherein the hydrogel precursor solution includes a polyvinyl alcohol solvent and a conductive polymer precursor and an oxidant dispersed in the polyvinyl alcohol;

[0030] S20, performing activation treatment on the electrode substrate to obtain an activated electrode substrate;

[0031] S30, coating the hydrogel precursor solution onto the surface of the activated electrode substrate, first performing a freeze-thaw cycle treatment, then performing a drying treatment, and finally performing a heat treatment to obtain an initial hydrogel electrode;

[0032] S40, immersing the initial hydrogel electrode in deionized water or PBS solution to obtain the hydrogel electrode with anti-fatigue bonding properties.

[0033] Specifically, current implantable electrodes (including: pacemakers, deep brain stimulation electrodes, etc.) are almost all metal electrodes (platinum, platinum alloys, etc.). The disadvantages of this type of electrode are high interface impedance and high rigidity, which can easily cause tissue damage. Therefore, hydrogels are usually used to modify the electrode interface. However, conventional hydrogel electrode coatings will cause the hydrogel coating to detach or rupture during long-term operation (electric pulses). The hydrogel electrode prepared by the present invention can not only reduce impedance and alleviate tissue damage, but most importantly, it has anti-fatigue bonding properties (the so-called anti-fatigue bonding means that the interface remains stable under long-term stress conditions), so it remains stable under long-term electrochemical cycles or electrical stimulation (electric pulses).

[0034] The hydrogel electrode prepared by the present invention has such characteristics because: polyvinyl alcohol (PVA) becomes a cross-linked network hydrogel during the freeze-thaw process, and then during the air-drying process, the hydrogel is intactly attached to the surface of the electrode substrate. After further thermal annealing, PVA crystallizes and generates a nanocrystalline area at the electrode substrate adhesion interface. The nanocrystalline area will hinder the expansion of cracks, thereby effectively preventing the electrode from breaking and detaching due to crack expansion during operation, ensuring the stability of the electrode during long-term application.

[0035] Specifically, during the freezing-thawing process, hydrogen bonds will form within and between PVA molecules, forming microcrystalline structures between molecules. These microcrystals serve as cross-linking points to form microgels. At the same time, this process is accompanied by phase separation, forming polymer focusing areas and non-aggregation areas, forming the internal network of the hydrogel. Polymer crystallization is the process of partial arrangement of polymer chains. During this process, the polymer chains fold up to form ordered areas, which become lamellae. When the temperature is between the melting point Tm and the glass transition temperature Tg, the folded molecular chains continue to increase, which is crystal growth. Too high a temperature will destroy the orderly arrangement of molecules, and the movement of the molecular chains will be frozen if the temperature is below the glass transition temperature. The growth of the crystallization area occurs preferentially in the direction with the largest temperature gradient and is inhibited by the amorphous areas at the top and bottom of the lamellae. If the gradient is large, the crystal growth direction is uncertain and grows into dendrites. If the temperature is relatively uniform and stable, the lamellae will grow radially and grow into spherulites. The same is true for the crystallization mechanism of PVA.

[0036] In some embodiments, the electrode substrate is a platinum electrode, a gold electrode, a stainless steel electrode, a magnesium electrode, ITO-glass, ITO-PET, a carbon electrode, and an electrode whose surface is coated with a conductive material, but is not limited thereto. The engineering material may be polyethylene, polyurethane, PET, PI, PC, PDMS, and the like.

[0037] In some embodiments, the step of cleaning and activating the electrode substrate comprises: immersing the electrode substrate in deionized water, ethanol, and acetone for ultrasonic cleaning, each ultrasonic cleaning for 5-15 minutes, repeated three times, and drying under nitrogen conditions to obtain a cleaned electrode substrate; oxygen plasma cleaning and activation treatment for 5-30 minutes are performed on the surface of the cleaned electrode substrate to obtain an activated electrode substrate. In this embodiment, the plasma surface treatment equipment is an effective surface cleaning, activation and coating treatment process, which can be used to treat various materials, including plastics, metals or glass. By cleaning the surface of the substrate with plasma, organic pollutants can be thoroughly cleaned in a short time, and the pollutants are pumped away by the vacuum pump, and the cleaning degree reaches the molecular level. In addition, oxygen plasma cleaning can change the characteristics of the substrate surface. After the plasma acts on the solid surface, the original chemical bonds on the solid surface are broken, and the free radicals (oxygen free radicals) in the plasma combine with these bonds. A large number of hydroxyl groups will be formed on the surface of the base, which effectively improves the hydrophilicity of the solid surface. It is conducive to the spreading of PVA on the electrode surface. At the same time, the hydroxyl groups inside PVA can form a large number of hydrogen bonds with the electrode, which is conducive to the adhesion of PVA to the base. Oxygen plasma will produce oxygen free radicals, which help to form hydroxyl groups on the electrode surface.

[0038] In some embodiments, the conductive polymer precursor is one or more of acetylene, thiophene, 3-methylthiophene, 3-hexylthiophene, aniline, aminophenylboronic acid, pyrrole, furan, indole, 5-nitroindole, 5-carboxylic acid indole, p-phenylene vinylene, 3,4-ethylenedioxythiophene, 2'-aminomethyl-3,4-ethylenedioxythiophene and hydroxymethyl (3,4-ethylenedioxythiophene), but is not limited thereto.

[0039] In some embodiments, the oxidant is one or more of iodine, ammonium persulfate, ferric chloride, ferric p-toluenesulfonate, hydrogen peroxide, potassium dichromate and potassium permanganate, but is not limited thereto.

[0040] In some embodiments, the polyvinyl alcohol solution is a polyvinyl alcohol aqueous solution with a mass fraction of 3%-20%, and the molecular weight of the polyvinyl alcohol is 1000-300000Da. In this embodiment, the upper limit of the mass percentage is determined based on the maximum solubility of PVA, and the maximum solubility of high molecular weight PVA is about 20%. The lower limit of the mass fraction is determined based on the lower limit of the function of PVA. When the mass fraction is lower than 3%, the bonding effect of PVA and the base will be significantly reduced.

[0041] In some embodiments, in the step of coating the hydrogel precursor solution onto the surface of the activated electrode substrate, the coating method includes drip coating, dip coating, spin coating, spray coating, scraping coating, printing and the like, and dip coating and scraping coating are further preferred.

[0042] In some embodiments, the freeze-thaw cycle treatment step includes: first freezing at a temperature of -30°C to 0°C for 5-8 hours, and then thawing at a temperature of 0°C to 40°C for 1-3 hours, and the number of cycles is 2-10 times; the drying treatment step includes: drying under air or nitrogen conditions for 3-48 hours; the heat treatment step includes: heating at a temperature of 60°C to 150°C for 0.5-24 hours.

[0043] In this embodiment, the freeze-thaw cycle will cause PVA to form a physically cross-linked hydrogel. As the number of freeze-thaw cycles increases, the cross-linking points in the sample increase, the cross-linking density increases, and more crystalline micro-regions appear, making the corresponding crystalline structure more complete. The annealing temperature has a great influence on the crystallinity of PVA. The freeze-thaw process will cause PVA to form microcrystalline regions, which will promote the growth of microcrystalline regions in the further annealing process to form larger crystalline regions. Crystal growth causes the amorphous region to become smaller. Temperature is the main factor that determines the growth of crystalline regions inside PVA. Too low a temperature is not conducive to the growth of crystalline regions. Too high a temperature will cause excessive crystallinity inside PVA or carbonization, thereby failing to form a hydrogel. Further increases in temperature may cause dissolution.

[0044] In some embodiments, a hydrogel electrode with anti-fatigue adhesion properties is also provided, wherein the hydrogel electrode is prepared using the preparation method of the hydrogel electrode with anti-fatigue adhesion properties described in the present invention, the hydrogel electrode includes an electrode substrate and a hydrogel coating bonded to the surface of the electrode substrate, and the material for preparing the hydrogel coating includes polyvinyl alcohol and a conductive polymer.

[0045] In this embodiment, the conductive polymer is one or more of polyacetylene, polythiophene, poly(3-hexylthiophene), polyaniline, polypyrrole, polyfuran, polyindole, poly(p-phenylene vinylene), poly(3,4-ethylenedioxythiophene) and poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate), but is not limited thereto.

[0046] In some embodiments, an application of a hydrogel electrode with anti-fatigue bonding properties is also provided, wherein the hydrogel electrode is used in an implantable biosensor, a cardiac pacemaker or a neural electrode. In the hydrogel electrode prepared by the present invention, since the PVA hydrogel has a high degree of crystallinity after thermal annealing, a high-energy unit (such as an ordered nanocrystalline domain) can be generated at the bonding interface, which can significantly improve the anti-fatigue performance of the hydrogel bonding and improve the interfacial fatigue threshold of the hydrogel, thereby ensuring a stable interfacial adhesion between the hydrogel coating and the electrode, as well as the anti-fatigue bonding characteristics in long-term operation. Therefore, the hydrogel electrode provided by the present invention can be applied to a variety of bioelectronic devices, such as implantable biosensors, cardiac pacemakers or neural electrodes, etc. The use of hydrogel-coated electrodes can effectively reduce the damage caused by the electrodes to biological tissues, and the hydrogel coating can effectively reduce the electrochemical impedance of the metal electrode.

[0047] The present invention is further explained below by specific embodiments:

[0048] Example 1

[0049] This embodiment provides a conductive hydrogel electrode with anti-fatigue bonding properties, and the preparation method thereof specifically includes the following steps:

[0050] (1) The platinum electrode was sequentially immersed in deionized water, ethanol, and acetone for ultrasonic cleaning for 10 min each time, repeated three times, and dried under nitrogen conditions;

[0051] (2) performing surface plasma cleaning and activation treatment on the cleaned electrode, with the activation time being 15 minutes;

[0052] (3) Dissolve PEDOT:PSS in a 10% PVA solution, stir rapidly, and centrifuge to degas;

[0053] (4) Soak the cleaned platinum electrode in the hydrogel precursor solution for 3 minutes, and then remove the electrode at a speed of 10 mm / min;

[0054] (5) The hydrogel electrode was sealed in a glass container and subjected to freeze-thaw cycles three times, with a freezing temperature of -20°C and a thawing temperature of 25°C;

[0055] (6) Place the hydrogel electrode in a nitrogen environment, dry for 24 h, and then anneal in an oven at 100 °C for 2 h;

[0056] (7) Soaking the hydrogel electrode in deionized water or PBS solution to obtain a conductive hydrogel electrode with anti-fatigue adhesion properties.

[0057] Example 2

[0058] (1) The gold electrode was sequentially immersed in deionized water, ethanol, and acetone for ultrasonic cleaning for 10 min each time, repeated three times, and dried under nitrogen conditions;

[0059] (2) performing surface plasma cleaning and activation treatment on the cleaned electrode, with the activation time being 30 minutes;

[0060] (3) dissolving aniline in a 20% by mass PVA solution, adding oxidant ferric chloride, rapidly stirring, and centrifuging for degassing;

[0061] (4) applying a drop of hydrogel precursor onto the surface of the gold electrode, with the coating thickness controlled at 100-120 μm;

[0062] (5) The hydrogel electrode was sealed in a glass container and subjected to 10 freeze-thaw cycles, with a freezing temperature of -5°C and a thawing temperature of 5°C;

[0063] (6) Place the hydrogel electrode in a nitrogen environment, dry for 3 h, and then anneal in an oven at 150 °C for 1 h;

[0064] (7) Soaking the hydrogel electrode in deionized water or PBS solution to obtain a conductive hydrogel electrode with anti-fatigue adhesion properties.

[0065] Example 3

[0066] (1) The ITO-glass electrode was sequentially immersed in deionized water, ethanol, and acetone for ultrasonic cleaning for 10 min each time, repeated three times, and dried under nitrogen conditions;

[0067] (2) performing surface plasma cleaning and activation treatment on the cleaned electrode, with the activation time being 5 minutes;

[0068] (3) dissolving pyrrole in a 3% by mass PVA solution, stirring rapidly, and centrifuging to degas;

[0069] (4) applying a drop of the hydrogel precursor onto the surface of the ITO-glass electrode, with the coating thickness controlled at 80-110 μm;

[0070] (5) The hydrogel electrode was sealed in a glass container and subjected to freeze-thaw cycles three times, with a freezing temperature of -30°C and a thawing temperature of 40°C;

[0071] (6) Place the hydrogel electrode in a nitrogen environment, dry for 48 h, and then anneal in an oven at 60 °C for 3 h;

[0072] (7) Soaking the hydrogel electrode in deionized water or PBS solution to obtain a conductive hydrogel electrode with anti-fatigue adhesion properties.

[0073] Example 4

[0074] (1) The ITO-PET electrode was sequentially immersed in deionized water, ethanol, and acetone for ultrasonic cleaning for 10 min each time, repeated three times, and then dried under nitrogen conditions;

[0075] (2) performing surface plasma cleaning and activation treatment on the cleaned electrode, with the activation time being 12 minutes;

[0076] (3) dissolving and dispersing 3,4-ethylenedioxythiophene in a 15% by mass PVA solution, adding oxidant ferric p-toluene acid, rapidly stirring, and centrifuging for degassing;

[0077] (4) applying a drop of hydrogel precursor onto the surface of the gold electrode, with the coating thickness controlled at 100-120 μm;

[0078] (5) The hydrogel electrode was sealed in a glass container and subjected to 5 freeze-thaw cycles, with a freezing temperature of -30°C and a thawing temperature of 30°C;

[0079] (6) Place the hydrogel electrode in a nitrogen environment, dry for 12 h, and then anneal in an oven at 80 °C for 5 h;

[0080] (7) Soaking the hydrogel electrode in deionized water or PBS solution to obtain a conductive hydrogel electrode with anti-fatigue adhesion properties.

[0081] Comparative Example 1

[0082] PEDOT:PSS was directly coated onto the surface of the platinum electrode and dried to form a PEDOT:PSS electrode.

[0083] Test Example 1

[0084] The adhesion properties of the hydrogel electrode prepared in Example 1 and the PEDOT:PSS electrode prepared in Comparative Example 1 to the hydrogel coating were tested. Figure 2 As shown. Figure 2 It can be seen that in the hydrogel electrode prepared in Example 1, the bonding toughness between the electrode and the hydrogel coating is about 350 Jm -2 The shear strength is about 260 kPa, while the bonding toughness between the electrode and the PEDOT:PSS layer in Comparative Example 1 is about 10 Jm -2 , the shear strength is about 10 kPa. Obviously, in the hydrogel electrode prepared in Example 1 of the present invention, the adhesion performance of the hydrogel coating to the electrode is much better than that of the PEDOT:PSS electrode in Comparative Example 1.

[0085] Test Example 2

[0086] The cyclic voltammetric stability of the hydrogel electrode prepared in Example 1 before and after ultrasound was tested, and the cyclic voltammetric curve of the hydrogel electrode was tested using a three-electrode system. The electrode coated with the hydrogel was used as the working electrode, the pure platinum electrode was used as the counter electrode, and the silver / silver chloride electrode was used as the reference electrode. The above electrodes were placed in a PBS solution, and the cyclic voltammetric characteristic curve of the hydrogel was measured by cyclic voltammetry. The voltage window was set between -0.3-0.5V to determine the electrical activity of the hydrogel; and the loss of the electrical activity of the hydrogel before and after mechanical ultrasound was compared.

[0087] Test results such as Figure 3 As shown, from Figure 3 The results show that the hydrogel coating prepared by the method of Example 1 will form a strong adhesion with the metal electrode, which can offset the shear stress generated by mechanical ultrasound and ensure the stability of the hydrogel coating on the electrode surface. The stability of the hydrogel on the electrode surface was tested by mechanical ultrasound. The working electrode coated with the hydrogel was immersed in a PBS solution and mechanically ultrasounded for 30 minutes. During the mechanical ultrasound process, strong shear stress will be generated between the metal electrode and the hydrogel. If the adhesion between the hydrogel and the base is insufficient, the strong shear stress generated by mechanical ultrasound will cause the electroactive hydrogel to fall off the electrode surface, thereby reducing the active substances on the electrode surface.

[0088] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A method for preparing a hydrogel electrode with anti-fatigue bonding properties, characterized in that: Includes steps: Providing an electrode matrix and a hydrogel precursor solution, wherein the hydrogel precursor solution includes a polyvinyl alcohol aqueous solution with a mass fraction of 10% and poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) dispersed in the polyvinyl alcohol solution; Performing an activation treatment on the electrode matrix to obtain an activated electrode matrix; The hydrogel precursor solution is applied to the surface of the activated electrode substrate, firstly subjected to a freeze-thaw cycle treatment, then subjected to a drying treatment, and finally subjected to a heat treatment to obtain an initial hydrogel electrode; Soaking the initial hydrogel electrode in deionized water or PBS solution, and taking out the hydrogel electrode with anti-fatigue bonding properties; The freeze-thaw cycle treatment step includes: first freezing at a temperature of -30°C to 0°C for 5-8 hours, then thawing at a temperature of 0°C to 40°C for 1-3 hours, and the number of cycles is 1-10 times; the drying treatment step includes: drying under air or nitrogen conditions for 3-48 hours; the heat treatment step includes: heating at a temperature of 60°C to 150°C for 0.5-24 hours.

2. The method for preparing a hydrogel electrode having anti-fatigue bonding properties according to claim 1, characterized in that: The electrode substrate is one of a platinum electrode, a gold electrode, a stainless steel electrode, a magnesium electrode, ITO-glass, ITO-PET and a carbon electrode.

3. The method for preparing a hydrogel electrode with anti-fatigue bonding properties according to claim 1, characterized in that: The electrode substrate is an electrode whose surface is coated with a conductive material.

4. The method for preparing a hydrogel electrode with anti-fatigue bonding properties according to claim 1, characterized in that: The step of activating the electrode substrate comprises: The electrode substrate is sequentially immersed in deionized water, ethanol, and acetone for ultrasonic cleaning, each ultrasonic cleaning lasts for 5-15 minutes, and repeated three times, and dried under nitrogen conditions to obtain a cleaned electrode substrate; The surface of the cleaned electrode substrate is cleaned with oxygen plasma and activated for 5-30 minutes to obtain an activated electrode substrate.

5. The method for preparing a hydrogel electrode with anti-fatigue bonding properties according to claim 1, characterized in that: The molecular weight of polyvinyl alcohol is 1000-300000 Da.

6. A hydrogel electrode with fatigue-resistant bonding properties, characterized in that: The hydrogel electrode with anti-fatigue bonding properties is prepared by the preparation method of any one of claims 1-5, wherein the hydrogel electrode comprises an electrode substrate and a hydrogel coating bonded to the surface of the electrode substrate, and the material for preparing the hydrogel coating comprises polyvinyl alcohol and a conductive polymer.

7. A use of the hydrogel electrode with anti-fatigue bonding properties as claimed in claim 6, characterized in that: Hydrogel electrodes are used to prepare implantable biosensors.

8. A use of the hydrogel electrode with anti-fatigue bonding properties as claimed in claim 6, characterized in that: The hydrogel electrode is used to prepare a cardiac pacemaker or a neural electrode.

Citation Information

Patent Citations

  • Polyvinyl alcohol-based conductive hydrogel as well as preparation method and application thereof

    CN113637181A